Evaluasi Dan Rekomendasi Perbaikan Desain Antarmuka Pengguna Menggunakan Metode Think Aloud Dan Pendekatan Human Centered Design (HCD) (Studi Kasus: Aplikasi iPusnas) - Arbi Ramadhan Akbar Asmanputra; Hanifah Muslimah Az-Zahra; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The National Library of Indonesia through the Data and Information Center (Pusdatin) in collaboration with Aksaramaya has a mission to make continuous improvements to the iPusnas application with the target of the iPusnas application version 2.0, with a new face that focuses more on user needs. This research was conducted to assist the National Library of Indonesia and Aksaramaya in providing recommendations for improving the user interface design of mobile-based applications on the Android platform using the Human Centered Design (HCD) approach supported by the think aloud method during the usability evaluation. Recommendations for improvements are made through the inspiration and ideation phases of the HCD approach. The inspiration phase focuses on finding usability problems that exist in the current iPusnas application by conducting a usability evaluation involving 15 participants. The results of the usability evaluation of the iPusnas application in the inspiration phase resulted in 11 main problems found by the participants. Giving solution ideas in the ideation phase resulted in a wireframe design for 21 features that needed to be improved, with the results of the wireframe evaluation there were 6 problems that were still felt by the participants. The final result of the research in the form of recommendations for user interface improvements is obtained after conducting an evaluation which found 11 problems in the user interface design which were made based on the results of the evaluation of the wireframe.